The behavior of frequency locking of ring oscillators with RF interference on the supply. (October 2021) - Zhang, Zhiwen; Yang, Simei; Su, Tao
Abstract: The response of a ring oscillator to radio-frequency interference on the power supply includes a frequency shift and jitter. This paper shows that under certain conditions, the interference of one phase on the supply can lock the ring oscillator—the frequency of the oscillator does not shift as the interference amplitude is increased. A theoretical framework is developed to calculate the locations of the locking ranges. Both transistor-level simulations and board-level measurements are performed to confirm the locking phenomenon. Some unique properties of the locking are demonstrated. First, multiple locking ranges exist. Second, the gate-level locking mode dominates the locking mechanism. Third, the locking strength is proposed to characterize the difference of the locking ranges. Fourth, the locking dynamics are analyzed and summarized by studying the evolution of the gate delay. Finally, three types of interferences in addition to sinusoidal interference are found able to lock the ring oscillator under the same gate-level locking mode.